Postawy etyczne pracowników administracji samorządowej - Stasiak, Ewelina (Annales. Etyka w Życiu Gospodarczym, 2016)
The purpose of the article is to present the appropriate ethical attitudes of local governmentemployees which affect the efficiency of the administration. Local governmentemployees who are exclusively competent and honest are able to properly executetheir goals within strictly defined procedures and tasks. The article focuses ona brief analysis of the concept of ethics, employees of local government, as well asan analysis of ethics in terms of its impact on the quality of services.